Efficacy and safety of intermittent theta-burst stimulation in patients with schizophrenia: A meta-analysis of randomized sham-controlled trials - Goh, Kah Kheng; Chen, Chun-Hsin; Wu, Tzu-Hua; Chiu, Yi-Hang; Lu, Mong-Liang (Frontiers in Pharmacology, 2022)
Theta-burst stimulation is a non-invasive brain stimulation technique that was introduced as a potential augmentation treatment for patients with schizophrenia. The purpose of this meta-analysis was to investigate the therapeutic efficacy and safety of intermittent theta-burst stimulation in patients with schizophrenia. Following the PRISMA guidelines, the MEDLINE, Embase, Cochrane, Scopus, Web of Science, and CNKI databases were searched for relevant studies from database inception to 9 January 2022. Change in symptom severity among patients with schizophrenia was the primary outcome, and changes in cognitive function and safety profiles, including the discontinuation rate and adverse events, were secondary outcomes. In total, 13 double-blind randomized sham-controlled trials with 524 patients were included. Intermittent theta-burst stimulation adjunct to antipsychotics was associated with significantly improved psychopathology in patients with schizophrenia, particularly for negative symptoms and general psychopathology but not for positive symptoms or cognitive function. The stimulation parameters influenced the effectiveness of intermittent theta-burst stimulation. A more favorable effect was observed in patients who received theta-burst stimulation at the left dorsolateral prefrontal cortex, with ≥1800 pulses per day, for ≥20 sessions, and using an inactive sham coil as a placebo comparison in the study. The intermittent theta-burst stimulation is well tolerated and safe in patients with schizophrenia. Intermittent theta-burst stimulation adjunct to antipsychotics treatment is associated with significant improvement in negative symptoms and favorable tolerability in patients with schizophrenia. This meta-analysis may provide insights into the use of intermittent theta-burst stimulation as an additional treatment to alleviate the negative symptoms of schizophrenia.